2021
DOI: 10.1039/d1tc04354d
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-stabilized bistable dual-frequency cholesteric liquid crystal devices assisted by a predesigned chiral dopant

Abstract: Fabricated polymer-stabilized bistable cholesteric liquid crystal devices show a stable opaque focal conic state and a stable transparent planar state without any energy consumption once they are turned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…6 In the synthesis of the helical polymers with chemical polycondensation in the CLC, the liquid crystal phase is maintained when the stirring speed and the type of liquid crystal are within an appropriate range. 7 The maintenance of the CLC phase is visually confirmed by iridescence from the liquid crystal surface as the reaction solution during the polymerization reaction. 2 The present study focuses on the use of monomers with chirality inductive function for preparing a CLC solvent from an achiral nematic liquid crystal during polymerization.…”
Section: ■ Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…6 In the synthesis of the helical polymers with chemical polycondensation in the CLC, the liquid crystal phase is maintained when the stirring speed and the type of liquid crystal are within an appropriate range. 7 The maintenance of the CLC phase is visually confirmed by iridescence from the liquid crystal surface as the reaction solution during the polymerization reaction. 2 The present study focuses on the use of monomers with chirality inductive function for preparing a CLC solvent from an achiral nematic liquid crystal during polymerization.…”
Section: ■ Introductionmentioning
confidence: 93%
“…Electrochemical and chemical polymerizations in CLCs have been achieved to obtain chiral π-conjugated polymers with helical structure . In the synthesis of the helical polymers with chemical polycondensation in the CLC, the liquid crystal phase is maintained when the stirring speed and the type of liquid crystal are within an appropriate range . The maintenance of the CLC phase is visually confirmed by iridescence from the liquid crystal surface as the reaction solution during the polymerization reaction .…”
Section: Introductionmentioning
confidence: 99%
“…23 Additionally, a chiral ferroelectric liquid crystal is designed to enhance the bistable performance. 24 Continuous research has demonstrated the progress in PSCT films with a reliable bistable property. Nevertheless, the intrinsic disadvantages of dual-frequency liquid crystals hinder their practical use, for instance, temperature sensitivity of the crossover frequency.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Bistable materials, which only consume negligible energy during the process of state-switching, have attracted attention due to their unique advantage of a high energy utilization rate. [4][5][6] Therefore, smart windows and some electronic displays constructed with these types of materials will be undoubtedly beneficial for global energy-saving and sustainability. [7][8][9][10][11][12] Bistable electrochromic devices (BECDs), whose optical properties can be dynamically regulated by applying an electric field reversibly, have been regarded as promising alternatives for future energy-saving devices [13][14][15][16][17] due to their advantages, such as low-cost preparation, high energy efficiency, outstanding optical modulation ability, etc.…”
Section: Introductionmentioning
confidence: 99%